A causal model of parenting stress among first-time adolescent mothers - Kingfa Sanglee (2020)
© 2019, Thailand Nursing and Midwifery Council. All rights reserved. Parenting stress affects maternal function and psychological health and development of their child. To prevent or minimize stress among adolescent mothers, understanding how various factors work to influence stress is necessary. Thus, this study aimed to develop and test a causal model of parenting stress in first-time adolescent mothers. A total of 253 first-time postpartum adolescent mothers accessing health services for checking up were recruited from nine hospitals in a northern province in Thailand. Nine instruments were used to collect data: The Parental Distress Subscale of the Parenting Stress Index/Short Form, the Modified Knowledge of Child Development Inventory, the Self-Perception of the Parenting Role Scale, the Parenting Sense of Competence Scale, the Revised Thai Multi-dimensional Scale of Perceived Social Support, the Family Economic Strain Scale, the Kansas Marital Satisfaction Scale, the Child-rearing Conflict Measure, and the What My Baby is Like Questionnaire. Data were analyzed using descriptive statistics, Pearson’s product moment correlation, and path analysis with LISREL. The causal model of parenting stress obtained the best fit with the data. This model could explain 75% of the total variance in parenting stress. Social support, parenting attitude and self-efficacy, and child temperament influenced parenting stress directly. Social support, marital satisfaction, economic strain, child-rearing conflict, and parenting knowledge, attitude, and self-efficacy also indirectly influenced parenting stress. Nurses should design the program for preventing parenting stress in first-time adolescent mothers by emphasis on promoting positive parenting attitude and perceiving adapted child temperament, enhancing parenting self-efficacy and social support.